Endocan and Interleukin-6 Levels in Individuals with polycystic ovary syndrome and periodontal inflammation: A prospective cross-sectional stud - Saglam, Ebru; Sebin, Engin; Toraman, Ayse; Canakci, Humeyra; Ingec, Metin; Fatih Canakci, Cenk (Annals of Medical Research, 2021)
Aim: Periodontitis and polycystic ovary syndrome (PCOS) are relationship to both chronic low-grade inflammation and systemic inflammation. In spite of common risk factors, the link between periodontitis and PCOS has not yet been clear. The aims of the current cross-sectional study are to determine serum and saliva endocan and interleukin-6(IL-6) levels, and to evaluate the correlation between these two biomarkers in women with periodontitis and PCOS. Materials and Methods: 87 individuals divided into four groups; PCOS with periodontitis (PCOSP), PCOS but periodontally healthy (PCOSPH), systemically healthy with periodontitis (SHP) and control group. Demographics, periodontal parameters, serum and saliva endocan and IL-6 values were evaluated. Results: Serum endocan values in all the study groups were significantly greater than those in the control group. Saliva endocan values in PCOSP group were greater than those in the control group. Serum IL-6 values in both the PCOSP and SHP groups were significantly greater than those in the control group. Saliva IL-6 values in both periodontitis groups were significantly greater than those in the control groups. There were significant positive correlations between the serum and saliva endocan and saliva IL-6 values (p0.01). Additionally, there was significant correlation between the saliva endocan and serum IL-6 levels (p0.05). Conclusion: Although both periodontitis and PCOS itself is increased endocan and IL-6 levels compared to those seen in healthy individuals, this increase was generally more pronounced in individuals with both PCOS and periodontitis. It can be thought that this increase may be modified by the inflammatory process in periodontal disease.